Tenderness and Structure of Chicken Meats with Papaya Extract Immersion (Carica papaya) - Bulkaini Bulkaini; B.R.D. Wulandani; I K Sumadi; Twenfosel O. Dami Dato (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2020)
The egg-laying chicken has a coarse texture with large fiber bonds, so it is classified as tough meat. The level of toughness of the meat can be improved by applying the compression technology using enzyme extracts such as papaya extract. The purpose of this study was to determine the effect of the level of use of papaya extract (Carica papaya) on the tenderness and structure of the rejected laying hens. The research material used was 4.500 g of egg rejected chicken meat and half-cooked papaya fruit extract. Meat tenderness testing is done by the Shear Press method, while observing the meat structure is done by microtechnical methods using binocular and digital microscopes. Data analysis of meat tenderness analysis with analysis of variance based on the Completely Randomized Design (CRD) of Unidirectional pattern with 4 treatments (P1= control, P2= 15%, P3= 30% dan P4= 45%) with 3 replications, while the meat structure was analyzed by calculating the average size of connective tissue and meat fibers in the form of millimicron units (ÃÂµm). The results showed that soaking papaya meat extract with different concentrations significantly affected (P<0.05) on the tenderness of laying hens. The tenderness of meat indicated by the value of meat breaking was ranges from 0.90 kg/cm2-1.36 kg/cm2. Observation of meat structure shows that the higher the concentration of papaya extract used to soak the meat, the connective tissue narrows and the muscle fibers widen.